2018
DOI: 10.3892/ijo.2018.4378
|View full text |Cite
|
Sign up to set email alerts
|

12(S)-HETE induces lymph endothelial cell retraction in�vitro by upregulation of SOX18

Abstract: Metastasising breast cancer cells communicate with adjacent lymph endothelia, intravasate and disseminate through lymphatic routes, colonise lymph nodes and finally metastasize to distant organs. Thus, understanding and blocking intravasation may attenuate the metastatic cascade at an early step. As a trigger factor, which causes the retraction of lymph endothelial cells (LECs) and opens entry ports for tumour cell intravasation, MDA-MB231 breast cancer cells secrete the pro-metastatic arachidonic acid metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Previous studies have reported that matrix metalloproteinase-1 activated the protein activated receptor 1 and Ca 2+ -release in LECs, inducing MLC2 and FAK, all of which are prerequisites for their retraction and CCID formation (6,12). In contrast, 12(S)-HETE has been indicated to activate the receptors 12-HETER, BLT2 and Ca 2+ -release (10,11), as well as the transcription factors NF-κB and SOX18 in LECs (18). NF-κB communicates with FAK in macrophages (26) and, conversely, NF-κB itself is controlled by FAK in endothelial and other types of cells (13,14).…”
Section: R E L a A N D S Ox 18 Reg U L A T E C O N S T I T U T I Ve A N D 12(s)-hete-induced Fak Phosphorylationmentioning
confidence: 94%
See 4 more Smart Citations
“…Previous studies have reported that matrix metalloproteinase-1 activated the protein activated receptor 1 and Ca 2+ -release in LECs, inducing MLC2 and FAK, all of which are prerequisites for their retraction and CCID formation (6,12). In contrast, 12(S)-HETE has been indicated to activate the receptors 12-HETER, BLT2 and Ca 2+ -release (10,11), as well as the transcription factors NF-κB and SOX18 in LECs (18). NF-κB communicates with FAK in macrophages (26) and, conversely, NF-κB itself is controlled by FAK in endothelial and other types of cells (13,14).…”
Section: R E L a A N D S Ox 18 Reg U L A T E C O N S T I T U T I Ve A N D 12(s)-hete-induced Fak Phosphorylationmentioning
confidence: 94%
“…This demonstrated that the constitutive expression of SOX18 and PROX1 were positively regulated by RELA in LECs. It has recently been demonstrated that RELA controls the 12(S)-HETE-stimulated upregulation of SOX18 and PROX1 (18). Since ICAM-1 is an accepted target of the NF-κB transcription factor in ECs (20,25), and specifically of RELA (18), the expression of ICAM-1 mRNA was examined, to control whether the activity of RELA was increased upon 12(S)-HETE-treatment of LECs (18) (Fig.…”
Section: (S)mentioning
confidence: 99%
See 3 more Smart Citations